Mast, a conserved microtubule-associated protein required for bipolar mitotic spindle organisation - Lemos, CL (2000)
Through mutational analysis in Drosophila, we have identified the gene multiple asters (mast), that encodes a new 165 kDa protein. mast mutant neuroblasts are highly polyploid and show severe mitotic abnormalities including the formation of mono- and multi-polar spindles organised by an irregular number of MTOCs of abnormal size and shape. The mast gene product is evolutionary conserved since homologues were identified from yeast to man, revealing a novel protein family. Antibodies against Mast and analysis of tissue culture cells expressing an EGFP-Mast fusion protein show that during mitosis this protein localises to centrosomes, the mitotic spindle, centromeres and spindle midzone. Microtubule-binding assays indicate that Mast is a microtubule-associated protein displaying strong affinity for polymerised microtubules. The defects observed in the mutant alleles and the intracellular localisation of the protein suggest that Mast plays an essential role in centrosome separation and organisation of the bipolar mitotic spindle.